Advances in silicon nitride ceramic biomaterials for dental applications ? A review - Mohammadi H.; Beddu S.; Petr? M.; Sepantafar M.; Ebadi M.; Yap B.K.; Bang L.T.; Yong T.C.; Ramesh S.; Rahimian Koloor S.S. (Elsevier Editora Ltda, 2025)
Titanium and its alloys have been utilized as the preferred material for dental implants due to its mechanical and biological performance leading to high clinical success rates. Nonetheless, ceramic-based dental implants have been developed as the demands for non-metallic dental restorations have increased. The advent of bioceramics has increased the possibility of resolution in regenerative processes challenges for dentistry applications. In this regard, silicon nitride (Si3N4) as a non-oxide ceramic has the potential for oral applications which is ground in its bactericidal properties. The present work aimed to shed light on Si3N4 ceramic being used for future dental applications. As a concluding remark, the bactericidal and immunomodulatory properties of Si3N4 together with its radiolucency are inferred as a suitable contender in oral cavity and dental applications. ? 2023 The Authors